2023
DOI: 10.1108/ilt-04-2023-0123
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model with nonuniform grids for the analysis of dynamic characteristics of scratched tilting-pad bearings

Bowen Fan,
Keke Yuan,
Wei Chen
et al.

Abstract: Purpose The purpose of this study is to present a numerical model for scratched tilting-pad bearings (STPBs) with nonuniform grids. In addition, the model is used to reveal the effects of the structural parameters of bearings on the dynamic characteristics of STPBs under impact loading. Design/methodology/approach By combining the Reynolds equation, the flow balance equation and the assumption of adiabatic bearings and shafts, a thermo-hydrodynamic model with nonuniform grids of scratched journal bearings wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The model of the block-on-ring system is shown in Figure 1 on bearing lubrication performance [30]. Jean et al [31,32] found that different scratch locations could change the fluid pressure distribution.…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of the block-on-ring system is shown in Figure 1 on bearing lubrication performance [30]. Jean et al [31,32] found that different scratch locations could change the fluid pressure distribution.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In fact, scratches may also appear on shaft surfaces, which is similar to the phenomenon whereby wear may occur both on the tool surface and the workpiece surface when the tool cuts the workpiece [29]. The scratches on the shaft surfaces will also significantly affect the bearing system, so scholars have started studying the influence of shaft scratches on bearing lubrication performance [30]. Jean et al [31,32] found that different scratch locations could change the fluid pressure distribution.…”
Section: Introductionmentioning
confidence: 99%